2015
DOI: 10.5424/sjar/2015134-8176
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Impact of the intensity of milk production on ammonia and greenhouse gas emissions in Portuguese cattle farms

Abstract: The aim of this study was evaluate the relationship between the intensity of milk production for a wide range of Portuguese commercial cattle farms and NH 3 and greenhouse gas (GHG) emissions from manure management and enteric fermentation. A survey was carried out at 1471 commercial dairy cattle farms (Holstein-Friesian) and the NH 3 , N 2 O and CH 4 emissions at each stage of manure management were estimated as well as CH 4 losses from enteric fermentation. Gaseous emissions were estimated by a mass flow app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Changes in the TMR, regarding the role of carbohydrates in reducing CH4 emissions are suggested by Haque et al [2014]. Pereira and Trindade [2015] indicated that besides the better feed-use and its improved digestibility, increased cow productivity in the surveyed farms significantly reduced emissions per 1 liter of milk. With capacity of 10.000 liters of milk per cow per year there was 25 percent less compared to the 6.600 liters per year.…”
Section: Possibilities Of Ghg and Ammonia Emission Reduction Feeding ...mentioning
confidence: 99%
“…Changes in the TMR, regarding the role of carbohydrates in reducing CH4 emissions are suggested by Haque et al [2014]. Pereira and Trindade [2015] indicated that besides the better feed-use and its improved digestibility, increased cow productivity in the surveyed farms significantly reduced emissions per 1 liter of milk. With capacity of 10.000 liters of milk per cow per year there was 25 percent less compared to the 6.600 liters per year.…”
Section: Possibilities Of Ghg and Ammonia Emission Reduction Feeding ...mentioning
confidence: 99%